Integrating genome-wide and epigenome-wide associations for antipsychotic induced extrapyramidal side effects - Kai Yao; Johan H. Thygesen; Siobhan K. Lock; Antonio F. Pardiñas; Antonia L. Pritchard; Israa Elbashir; Abdullah Lodhi; Zain-Ul-Abideen Ahmad; Michael C. O’Donovan; Michael J. Owen; James T. R. Walters; David St Clair; et al. (Psychopharmacology, 2026)
Rationale Antipsychotic medications are the first-line treatment for schizophrenia. Around 40% of people who are treated with antipsychotics could develop extrapyramidal side-effects (EPSE) including: (1) Dyskinesia, (2) Parkinsonism, (3) Akathisia, and (4) Dystonia. Objectives This study aimed to identify genetic risk factors for EPSE presence following antipsychotic treatment. Methods We conducted Genome-wide association (GWAS) and Epigenome-wide association (EWAS) meta-analyses of EPSE, with subset analyses separating first and second generation antipsychotic (FGA/SGA) exposure. We integrated significant EWAS findings from a between-case design to a comparable GWAS for association enrichment. We investigated whether polygenic risk scores (PRS) for schizophrenia, Parkinson’s disease, and Lewy-body dementia could predict EPSE. Results The primary GWAS top SNP rs2709733 (A/G) ( p = 5.755 × 10 −07 ) mapped to a long intergenic non-protein coding RNA, LINC01162 with consistent effects across all cohorts. Subset analyses with distinct FGA exposure indicated suggestive genes such as NAV2 , NRG3 , LSAMP and SGA exposure indicated SHISA9 and CNBD1 which are relevant for schizophrenia, autism, and epilepsy. In our primary EWAS, the most significant differentially methylated position (DMP) was cg05599348 (3.181 × 10 −07 ), located at chrX:103,174,718 (hg19) mapping to TMSB15B . Comparing EPSE cases to healthy controls, we identified nine DMPs associated with EPSE. The DMP cg12044923 (chr2:241453995, hg19), located within the STK32B gene, showed significant enrichment for EPSE association (permutation p = 0.010). STK32B is relevant to both psychiatric and movement disorders, suggesting potential shared mechanisms. Conclusions Our study sheds new light on the potential biological mechanisms underlying EPSE development in schizophrenia, highlighting the importance of exploring both methylation changes and SNP associations.

Nuclear and organellar phylogenies provide insights into evolutionary history and species boundaries in Galdieria - Manuela Iovinella; Sarah C.L. Lock; Luke C.M. Mackinder; James P.J. Chong; Georg A. Feichtinger; Sally James; Daniel Jeffares; Antonino Pollio; Emanuele Del Guacchio; Hwan Su Yoon; Claudia Ciniglia; Seth J. Davis (Algal Research, 2026)

Symbiodiniaceae and Bacterial Microbiome Dynamics Differentially Impact the Survival of Dominant Reef‐Flat Porites Corals - Colin Lock; Therese C. Miller; Colin J. Anthony; Héloïse Rouzé; James Fifer; Grace McDermott; Carlos A. Tramonte; Loreto Paulino; Sarah W. Davies; Laurie Raymundo; Bastian Bentlage (Environmental Microbiology, 2025)
Coral reefs face significant threats across the globe, prompting a surge in restoration efforts aimed at mitigating their global decline. The health, resilience, and adaptability of corals are greatly influenced by their microbial communities, and while the response of coral microbiomes to many environmental stressors has been extensively studied, less is known about their natural dynamics following transplantation, which is an essential process for restoring degraded reef habitats. In this study, we integrated DNA metabarcoding (16S & ITS2) with ecological monitoring to investigate the dynamics of Symbiodiniaceae and bacterial communities in two dominant coral spp., Porites lobata and Porites cylindrica , and their different colour morphs, as they underwent transplantation and an 18‐week acclimatisation period. We saw significant differences in microbial communities between the two Porites spp., outplanting sites, and individual coral colonies, as well as a colour morph‐related difference in P. lobata bacterial communities. We saw reduced relative abundances of Endozoicomonadaceae, specifically from the genus Parendozoicomonas, following transplantation. P. lobata colonies with later Symbiodiniaceae shifts (18 weeks) had lower long‐term survival. Changes in Symbiodiniaceae and bacterial communities have implications for holobiont function and colony survival, which should be considered when designing and implementing coral reef rehabilitation projects.

A corallimorpharian barren in southwestern Kochi, Japan - James Davis Reimer; Fabian Gösser; Kenta C. F. Kondo; Stephane De Palmas; Daito Yamaguchi; Maria Beger; Brigitte Sommer; Fiona Chong; Camille Burke; Ayaka Umeda Paul; James Lock; Takuma Mezaki (Marine Biodiversity, 2025)

Fish as environmental sentinels for metal contaminants of human health concern in the Lower Mississippi River Basin - Scoty Hearst; Trent Selby; Joseph Kazery; Steven Everman; Manliang Feng; Lillian Sisson; Chinaza Nwaiwu; Alison Cevallos; James Lock; Matthew Sinclair (Journal of Trace Elements in Medicine and Biology, 2025)

Future feed resources in sustainable salmonid production: A review - Sissel Albrektsen; Raine Kortet; Peter Vilhelm Skov; Elisabeth Ytteborg; Susanne Gitlesen; Dorinde Kleinegris; Liv‐Torunn Mydland; Jon Øvrum Hansen; Erik‐Jan Lock; Turid Mørkøre; Philip James; Xinxin Wang; et al. (Reviews in Aquaculture, 2022)
Aquaculture is one of the most resource‐efficient and sustainable ways to produce animal protein. The Food and Agriculture Organization predicts that cultivated aquatic species will provide around 53% of the world's seafood supply by 2030. Further growth of intensive farmed aquatic species may be limited by a shortage of feed resources. The aquaculture sector therefore needs to intensify its search for alternative ingredients based on renewable natural resources. A significant increase in production will require an accelerated transition in technology and production systems, better use of natural available resources, development of high‐quality alternative feed resources and exploitation of available space. The present review discusses the urgent need to identify appropriate alternative ingredients for a sustainable future salmonid production. We describe and evaluate the most promising marine ingredients, including low‐trophic species (mesopelagic fish, zooplankton, polychaetes, macroalgae and crustaceans), novel microbial ingredients (bacteria, yeast and microalgae), insects (black soldier fly, yellow meal worm and crickets), animal by‐products (poultry meal, meat and bone meal, blood meal and hydrolysed feather meal) and by‐products from other commercial productions (trimmings and blood). Furthermore, we discuss the available volumes and need for new processing technologies and refining methods to ensure commercial production of nutritionally healthy ingredients. The essential production steps and considerations for future development of sustainable and safe seafood production are also discussed.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Nesting, sleeping, and nighttime behaviors in wild and captive great apes - James R. Anderson; Mabel Y. L. Ang; Louise C. Lock; Iris Weiche (Primates, 2019)

Prioritising islands in the United Kingdom and crown dependencies for the eradication of invasive alien vertebrates and rodent biosecurity - Andrew Stanbury; Sophie Thomas; James Aegerter; Andy Brown; David Bullock; Mark Eaton; Leigh Lock; Richard Luxmoore; Sugoto Roy; Stan Whitaker; Steffen Oppel (European Journal of Wildlife Research, 2017)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)